Effect of Mobile Carrier on the Performance of PVAm–Nanocellulose Facilitated Transport Membranes for CO2 Capture - Riccardo Casadei; Elham Firouznia; Marco Giacinti Baschetti (Membranes, 2021)
Facilitated transport membranes obtained by coupling polyvinylamine with highly charged carboxymethylated nanocellulose fibers were studied considering both water sorption and gas permeation experiments. In particular, the effect of the L-arginine as a mobile carrier was investigated to understand possible improvements in CO2 transport across the membranes. The results show that L-arginine addition decreases the water uptake of the membrane, due to the lower polyvinylamine content, but was able to improve the CO2 transport. Tests carried on at 35 °C and high relative humidity indeed showed an increase of both CO2 permeability and selectivity with respect to nitrogen and methane. In particular, the CO2 permeability increased from 160 to about 340 Barrer when arginine loading was increased from 0 to 45 wt%. In the same conditions, selectivity with respect to nitrogen was more than doubled, increasing from 20 to 45. Minor improvements were instead obtained with respect to methane; CO2/CH4 selectivity, indeed, even in presence of the mobile carrier, was limited to about 20.